2019
DOI: 10.1128/aem.02479-18
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Rapidly Alters Microbiome Composition and Gene Transcription in the Clownfish Gut

Abstract: Diet is a major determinant of intestinal microbiome composition. While studies have evaluated microbiome responses to diet variation, less is understood about how the act of feeding influences the microbiome, independent of diet type. Here, we use the clownfish Premnas biaculeatus, a species reared commonly in ornamental marine aquaculture, to test how the diversity, predicted gene content, and gene transcription of the microbiome vary over a 2-day diurnal period with a single daily feeding event. This study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 66 publications
(68 reference statements)
1
46
0
Order By: Relevance
“…454 pyrosequencing platform. Parris et al 2018 Diet was a major destabilizing event for Clownfi sh gut microbiota, where signifi cant diff erences in microbial communities, predicted gene content, and gene transcription were noted immediately before and 90 min post feeding.…”
Section: Referencesmentioning
confidence: 99%
“…454 pyrosequencing platform. Parris et al 2018 Diet was a major destabilizing event for Clownfi sh gut microbiota, where signifi cant diff erences in microbial communities, predicted gene content, and gene transcription were noted immediately before and 90 min post feeding.…”
Section: Referencesmentioning
confidence: 99%
“…Of note, dosens of ESVs filtered out as chloroplastid were mostly derived from the feed (~13.7% of total reads), but barely detected in gut (~0.1%). Such disproportion indicates that the overrepresent feedborne bacteria in the gut of slow growth fugu were not exclusively due to the influx of DNA from dead or dormant cells (19). Rather, bacteria such as Pseudomonas, optimized to grow at high nutrient as copiotroph (with 6~10 average 16S rRNA copy number) (58), are known to be more competitive than oligotrophy in rapid growing or efficiently utilizing resource in the intestinal environment.…”
Section: Effects Of Feed-borne Bacteria On Gut Microbiota Differed Ammentioning
confidence: 99%
“…These findings offer support for our observations that proportions of feed source signals in gut microbiota was negatively correlated with fugu growth rate, which could be largely due to the inconsistent gastric evacuation rate among different sized hosts. Several studies had suggested that the feed associated microbiota could play a crucial role in host health and nutrition (18,19,61), yet little is know about the functional impact and the extent to which it exerted. Herein, BugBase predicted the gut of slow growth fugu (with higher feed source signal) to have significantly more bacteria that are potentially pathogenic and biofilms forming than other fish clusters ( Figure 3).…”
Section: Effects Of Feed-borne Bacteria On Gut Microbiota Differed Ammentioning
confidence: 99%
See 2 more Smart Citations